2018
DOI: 10.3892/ol.2018.8124
|View full text |Cite
|
Sign up to set email alerts
|

HER4 isoform CYT2 and its ligand NRG1III are expressed at high levels in human colorectal cancer

Abstract: Abstract. The present study aimed to evaluate the expression of human epidermal growth factor receptor (HER4) isoforms and their ligand neuregulin 1 (NRG1) isoforms in human primary colorectal cancer (CRC). The mRNA expression of HER4 isoforms JM-a, JM-b, CYT1 and CYT2, and their ligand isoforms NRG1 I, II and III in CRC tissues and adjacent normal tissues were quantified by reverse transcription-quantitative polymerase chain reaction analysis. Univariate analysis and logistic regression analysis were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…Our results showed that CRC patients with high expressions of CXCL1, MS4A2, HDC, NRG1, and IL13 had a better OS. A number of recent studies found that CXCL1, MS4A, NRG1 and IL13 were highly expressed in a variety of tumors (22)(23)(24)(25)(26)(27). These results are not consistent with our research, and thus their unknown mechanism in CRC needs to be further explored.…”
Section: Discussioncontrasting
confidence: 84%
“…Our results showed that CRC patients with high expressions of CXCL1, MS4A2, HDC, NRG1, and IL13 had a better OS. A number of recent studies found that CXCL1, MS4A, NRG1 and IL13 were highly expressed in a variety of tumors (22)(23)(24)(25)(26)(27). These results are not consistent with our research, and thus their unknown mechanism in CRC needs to be further explored.…”
Section: Discussioncontrasting
confidence: 84%
“…Wang et al (11) showed that Her4 expression promotes osteosarcoma cell proliferation and tumorigenesis, and reduced apoptosis both in vitro and in vivo. in our previous study, cYT-2, but not cYT-1, could significantly promote CRC progression (12).…”
Section: Introductionmentioning
confidence: 71%
“…Additionally, NRG1 has been shown to promote the progression in breast cancer ( Tsai et al, 2003 ; Cheng et al, 2009 ; Momeny et al, 2015 ; Shu et al, 2022 ). NRG1III was upregulated in CRC but its exact role in CRC is uncertain ( Guo et al, 2018 ). GAP43 was shown to be a “growth” or “plasticity” protein, promoting neuronal growth and regenerating axons ( Piontek et al, 2002 ; Hocquemiller et al, 2010 ; Zhao et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%